PENDIDIKAN AKHLAK DITAMAN ASUH HALIMATUSSA’DIYYAH UNTUK MENINGKATKAN KECERDASAN SPIRITUAL ANAK USIA DINI - Siti Nurlela; Hanifah Hanifah (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2023)
This research aimed to investigate the implementation of moral education to develop spiritual intelligence in children aged 4-5 years at Taman Asuh (foster garden) Halimatussa’diyyah Cibalung Village. This type of research was descriptive qualitative research.The results show that the implementation of moral education to develop spiritual intelligence in children aged 4-5 years at Taman Asuh (foster garden) Halimatussa’diyyah Cibalung Village includes planning, implementation, and evaluation. Moral education planning through the preparation of annual programs, semester programs, Weekly Learning Implementation Plans (RPPM), and Daily Learning Implementation Plans (RPPH). Implementation of moral education through exemplary, learning and habituation methods. Evaluation of moral education using assessment sheets and monitoring books.Taman Asuh (foster garden) Halimatussa’diyyah Cibalung Village is an institution consistent in developing all aspects of early childhood development, especially spiritual development based on Islamic values and the Standard Level of Child Development Achievement (STPPA).